Innate immune cell networking in hepatitis C virus infection. Issue 5 (7th July 2014) - Saha, Banishree; Szabo, Gyongyi
Abstract : Review on interactions among cells of the innate immune system during chronic Hepatitis C virus infection, and their effects on the disease outcome. ABSTRACT: Persistent viral infection, such as HCV infection, is the result of the inability of the host immune system to mount a successful antiviral response, as well as the escape strategies devised by the virus. Although each individual component of the host immune system plays important roles in antiviral immunity, the interactive network of immune cells as a whole acts against the virus. The innate immune system forms the first line of host defense against viral infection, and thus, virus elimination or chronic HCV infection is linked to the direct outcome of the interactions between the various innate immune cells and HCV. By understanding how the distinct components of the innate immune system function both individually and collectively during HCV infection, potential therapeutic targets can be identified to overcome immune dysfunction and control chronic viral infection.